Thermal fatigue behaviour and damage development in Al‐Alloys 6061 an 6061‐metal matrix composites. Issue 3 (March 2014) - Heimann, S.; Pohl, M.
<x xml:space="preserve">Abstract</x> Metal matrix composites (MMC) have become important materials in many technical fields. But above all there is a high amount of failures due to alternating stresses because of temperature changes. In this investigation the thermal fatigue behaviour of two metal matrix composites with different particle contents and their base material without particles are compared. It is shown that there are three main parameters influencing lifetime: the maximum temperature of the cycles, the particle content and the particle size. An increasing of these parameters means a decreasing of the cycle numbers before damage occurs.